Periodesasi Penulisan Hadis Nabi Saw - Iskandar, Muhammad (DIRAYAH : Jurnal Ilmu Hadis, 2020)
Writing the traditions of the Prophet Muhammad or in Arabic terms al-kitâbah has occurred since the time of the Prophet SAW lived. Although there are some controversies about his ability. But the process of writing the hadith itself occurred during the time of the Prophet Muhammad, as well as writing the Qur'an also took place. This is the fact. The codification or in Arabic is called at-tadwîn is an effort to collect the traditions of the Prophet Muhammad both originating from the notes and memorization of the muhaddist, then then the validity of both the sides of the Sanad and the eyes and finally collected in one book. In this paper, the author will explain the stages of writing the hadith of the Prophet SAW since the Prophet SAW was still alive until the codification of hadith at the end of the first century hijiriyah. Among the things that will be discussed in this study is the understanding of the scholars of the traditions of the Prophet Muhammad about the prohibition and skill of writing the traditions of the Prophet SAW. Because this has been a matter of debate even today. Also very important to explain is the role of the Companions in maintaining the authenticity of the hadith of the Prophet after his death. In this study, it will be explained the persistence of the Companions and Tabinin in making a very rigorous selection in accepting a history that was based on the Prophet Muhammad. This attitude is also the forerunner to the emergence of sanad sciences. The condition of the Islamic community played a role in the codification of the hadith of the Prophet. The year of the death of the third caliph in Islam Uthman bin Affan in 35 H was known as the year of slander, after which the Muslims began to split into several groups. This turned out to have an impact on the emergence of false traditions among Muslims with the aim of seeking justification for their group. Likewise with the emergence of kalam science, schools of fiqh, bigotry towards tribes as well as in Islamic societies, many have caused the emergence of false traditions. Penulisan hadis-hadis Rasulullah SAW atau dalam istilah bahasa arab al-kitâbah sudah terjadi sejak masa Nabi SAW hidup. Walaupun terdapat beberapa kontroversi tentang kebolehannya. Namun proses penulisan hadis itu sendiri terjadi pada Masa Rasulullah SAW, sebagaimana penulisan al-Qur’an juga terjadi. Ini adalah faktanya. Adapun kodifikasi atau dalam bahasa arab disebut at-tadwîn merupakan upaya mengumpulkan hadis-hadis Rasulullah SAW baik yang bersumber dari catatan-catatan maupun hafalan para muhaddist, lalu kemudian diteliti validitasnya baik dari sisi sanad maupun mata dan akhirnya dikumpulkan dalam satu kitab. Di dalam tulis ini, penulis akan memaparkan tahapan-tahapan penulisan hadis Nabi SAW sejak Nabi SAW masih hidup sampai terjadinya kodifikasi hadis pada akhir abad pertama hijiriyah. Di antara hal yang akan dikupas dalam kajian ini adalah pemahaman ulama terhadap hadis-hadis Rasulullah SAW tentang larangan dan kebolehan menulis hadis Nabi SAW. Karena hal ini menjadi hal yang diperdebatkan bahkan sampai saat ini. Hal yang juga sangat penting untuk dipaparkan adalah peran para sahabat dalam menjaga keautentikan hadis Nabi SAW setelah wafatnya beliau. Dalam kajian ini akan dipaparkan kegigihan para sahabat dan tabi’in melakukan seleksi yang sangat ketat dalam menerima suatu riwayat yang disandarkan kepada Rasulullah SAW. Sikap ini juga merupakan cikal bakal munculnya ilmu-ilmu kajian sanad. Kondisi masyarakat Islam turut berperan dalam terjadinya kodifikasi hadis Nabi SAW. Tahun wafatnya khalifah ketiga dalam Islam Utsman bin Affan pada tahun 35 H dikenal dengan tahun fitnah, dimana setelah itu umat Islam mulai terpecah dalam beberapa kelompok. Hal ini ternyata berdampak pada munculnya hadis-hadis palsu di kalangan umat Islam dengan tujuan untuk mencari pembenaran terhadap kelompoknya. Begitu juga dengan kemunculan ilmu kalam, mazhab-mazhab fiqh, kefanatikan terhadap suku juga di dalam masyarakat Islam telah banyak menyebabkan munculnya hadi-hadis palsu.